(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe psychological distress and associated factors among patients with esophageal cancer. Methods: A cross-sectional study of patients ≥18 years treated at the Department of Pain Management and Palliative Care, 108 Military Central Hospital. Distress was assessed using the Distress Thermometer; demographic, clinical, and treatment data were analyzed. Results: Mean DT score was 4.0 ± 2.12; 52.6% had DT ≥4. Most had moderate distress. Main sources were physical symptoms, emotional problems, and financial burden. Associated factors included age ≤60, prior cancer treatment, and chemotherapy. Conclusion: Routine screening and comprehensive psychosocial support are recommended.